FRI0233 Real-World Treatment Persistence and Clinical Outcomes of TNFI Cycling vs Switching To New Mechanism-of-Action Dmards among Patients with Rheumatoid Arthritis in The United States. (15th July 2016) - Wei, W.; Knapp, K.; Wang, L.; Chen, C.; Craig, G.; Ferguson, K.; Schwartzman, S.
Abstract : Background: Recent studies suggested that in rheumatoid arthritis (RA) patients discontinuing their prior tumor necrosis factor inhibitor (TNFi), treatment persistence was greater in those switching to a disease-modifying antirheumatic drug (DMARD) with a new mechanism-of-action (MOA) than in those cycling to a second TNFi. Objectives: To evaluate in RA patients real-world treatment persistence and clinical outcomes associated with TNFi cycling vs switching to a new MOA DMARD. Methods: This retrospective analysis of RA patients used the US clinical JointMan® database, an evidence-based rheumatology software application that rheumatologists use to systematically document patient-level data in routine clinical practice. Adult RA patients were included if they had a physician prescription record of a TNFi from April 1, 2010 through March 31, 2015 and a subsequent DMARD that was a different TNFi (TNFi cycling cohort) or new MOA DMARD (new MOA DMARD switching cohort). Patients were indexed on the date of the subsequent TNFi or new MOA DMARD from a prior TNFi during the pre-index period. Treatment persistence was assessed, defined as neither discontinuing nor switching the drug post-index before the end of the observational period. Change in Clinical Disease Activity Index (CDAI) at 1 year post-index and its correlation with treatment persistence were evaluated. Kaplan-Meier survival analysis measured time to nonpersistence. Cox proportional hazards regression and ordinary least-squares regression were used to identify independent factors predicting time to nonpersistence and 1-year CDAI change, respectively. Results: Included were 613 patients (mean age 56.5 years; 78.5% women; 82.9% white; baseline CDAI 22.7). After discontinuing a prior TNFi, 54.2% (n=332) of patients cycled to another TNFi and 45.8% (n=281) switched to a new MOA DMARD. During follow-up, 36.7% (n=225) of patients were persistent with their index drug, 34.1% (n=209) switched from their index drug to another drug, and 29.2% (n=179) discontinued their index drug. Compared with TNFi cyclers, new MOA DMARD switchers were more likely to be persistent at 1 year (45.2% vs 29.5%; P <0.0001) and to persist for a longer period of time (Figure 1 ). After adjusting for covariates, TNFi cyclers were more likely to be nonpersistent than new MOA DMARD switchers (adjusted hazard ratio 1.511; P <0.001). Reduction in CDAI at 1 year was lower in TNFi cyclers than in new MOA DMARD switchers (−4.73 vs −7.64; P =0.027); however, this effect was not statistically significant when baseline CDAI was controlled for in the regression model (−5.83 vs −6.39; P =0.607). Overall, treatment persistence was associated with a significantly higher reduction in CDAI (−8.69 vs −3.16; P <0.001). Conclusions: This real-world study suggests that after discontinuing their prior TNFi, RA patients who switched to a new MOA DMARD demonstrated better treatment persistence than those cycling to another TNFi. Persistence with RA treatment was associated with better clinical outcome. Acknowledgement: Research sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Editorial assistance provided by I. Ouwehand, PhD, of Excerpta Medica, funded by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interest: W. Wei Shareholder of: Sanofi, Employee of: Sanofi, K. Knapp Employee of: Arthritis Northwest and Discus Analytics, Inc., L. Wang Consultant for: Sanofi and Regeneron Pharmaceuticals, Inc., Employee of: STATinMED research, C. Chen Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc., G. Craig Shareholder of: Discus Analytics, Inc., Employee of: Arthritis Northwest and Discus Analytics, Inc., K. Ferguson Shareholder of: Discus Analytics, Inc., Employee of: Arthritis Northwest and Discus Analytics, Inc., S. Schwartzman Shareholder of: Discus Analytics, Inc., Consultant for: Discus Analytics, Inc.